Neonatal Hypoglycemia in Women Controlled Intrapartum With Insulin Pump as Compared to Subcutaneous Insulin & Drip [18R]. (May 2017) - Soni, Shelly; Shah, Nikita; Rochelson, Burt; Simmonds, Lisa
Abstract : INTRODUCTION: To evaluate the incidence of neonatal hypoglycemia in women with diabetes whose intrapartum insulin management is controlled with continuous insulin pump as compared with those managed with subcutaneous insulin as well as drip. METHODS: Retrospective review of patients with pregestational Type 1 and 2 diabetes. Primary outcome was neonatal hypoglycemia, defined as neonatal blood glucose levels of < than 40 mg/dl in the first 24 hrs. Patients were categorized into groups — those receiving intrapartum subcutaneous insulin as well as drip and those with intrapartum insulin pumps. Elective cesarean sections were excluded. RESULTS: 102 patients were included. 71 had type 2 diabetes and 30.4% had type 1 diabetes. There was a greater rate of neonatal hypoglycemia in patients receiving subcutaneous/insulin drip, the difference was not statistically significant (28.6% vs 15.6%, p=0.2). There was no difference in the other perinatal outcomes; cesarean deliveries, birth weights, NICU admissions and the need of neonatal intravenous glucose. There were more patients with Type 1 diabetes in the pump group. Periconception HbA1C was similar. Though birth weights were higher in the pump group, the rate of hypoglycemia as well as the need of intravenous glucose was lower. Our data may have been biased because of more Type 1 diabetics in the pump group. CONCLUSION: We found no statistical difference in neonatal outcomes of patients receiving intrapartum continuous subcutaneous insulin infusion pump and those on subcutaneous insulin or drip. Continuing these patients on pump is a reasonable option, especially with lower rates of neonatal hypoglycemia and need of intravenous glucose.